2016
DOI: 10.1128/mbio.01397-16
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae Siderophores Induce Inflammation, Bacterial Dissemination, and HIF-1α Stabilization during Pneumonia

Abstract: Klebsiella pneumoniae is a Gram-negative pathogen responsible for a wide range of infections, including pneumonia and bacteremia, and is rapidly acquiring antibiotic resistance. K. pneumoniae requires secretion of siderophores, low-molecular-weight, high-affinity iron chelators, for bacterial replication and full virulence. The specific combination of siderophores secreted by K. pneumoniae during infection can impact tissue localization, systemic dissemination, and host survival. However, the effect of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 58 publications
6
117
0
5
Order By: Relevance
“…The ability of a bacterium to secrete more than one type of siderophore enhances its ability to colonize the GIT and prevent neutralization of one siderophore by the host. The most prevalent siderophore secreted by K. pneumoniae is enterobactin due to its high affinity for iron …”
Section: Pathogenic Mechanisms and Virulence Factors Of K Pneumoniae Imentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of a bacterium to secrete more than one type of siderophore enhances its ability to colonize the GIT and prevent neutralization of one siderophore by the host. The most prevalent siderophore secreted by K. pneumoniae is enterobactin due to its high affinity for iron …”
Section: Pathogenic Mechanisms and Virulence Factors Of K Pneumoniae Imentioning
confidence: 99%
“…The colibactin toxin that is released from K. pneumoniae is mediated by the polyketide synthases ( PKS ) gene. The colibactin toxin is known to cause DNA double‐strand breaks which induce genomic instability as well as cell cycle arrest . Similarly, the continuous insult of the colibactin toxin supplemented with the influx of proinflammatory cytokines into the colonic microenvironment leads to chronic inflammation.…”
Section: K Pneumoniae‐associated Diseases Of the Lower Gitmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, pathogenic bacteria have been shown to recognize HIF1α and respond to its accumulation with enhanced virulence (29) and to further enhance HIF1α production in host tissues (46, 47). As such, the accumulation of HIF1α in our model may serve as a quorum sensing signal for A. baumannii , enhancing its virulence and leading to wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Holden et al demonstrated that enterobactin stabilizes HIF-1α in respiratory cells in vitro , thereby inducing expression of proinflammatory cytokines and enhancing lipocalin-2-mediated inflammation (16). In a more recently published mBio article by Holden et al (17), the authors hypothesized that siderophores secreted by K. pneumoniae during lung infection can also have proinflammatory effects by interacting with host cells, thereby promoting pathogenicity during pneumonia.…”
Section: Commentarymentioning
confidence: 99%